Degrees of Truth: Engineering L. Ron Hubbard - Camacho, Ian C. (The journal of CESNUR, 2018)
Religious scholars Hugh B. Urban, Kjersti Hellesøy, Dorthe Refslund Christensen and Stephen A. Kent have forwarded the popular narrative that L. Ron Hubbard’s official biography is a hagiography. This consensus resulted partly from contrasting Hubbard’s incomplete, poor academic records against his purported claims about graduating from George Washington University with a civil engineering degree and good grades. By not closely inspecting all source materials, however, these scholars have missed the discrepancy causes: transcription errors that evolved, ultimately resulting in misattribution of authorship. Only religious scholar J. Gordon Melton has correctly noted in his book The Church of Scientology that Hubbard made no such claims, although Melton provided no detailedexplanation for the basis of his argument. Indeed, Hubbard directly addressed flunking and his poor grades in several places. This article not only expands on Melton’s observation, but posits that the prevailing view in which Hubbard claimed to have a civil engineering degree and good grades has actually resulted from incomplete and biased research.